2021
DOI: 10.3390/genes12091401
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing in a Series of Patients with a Clinical Diagnosis of Tuberous Sclerosis Not Confirmed by Targeted TSC1/TSC2 Sequencing

Abstract: Background: Approximately fifteen percent of patients with tuberous sclerosis complex (TSC) phenotype do not have any genetic disease-causing mutations which could be responsible for the development of TSC. The lack of a proper diagnosis significantly affects the quality of life for these patients and their families. Methods: The aim of our study was to use Whole Exome Sequencing (WES) in order to identify the genes responsible for the phenotype of nine patients with clinical signs of TSC, but without confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This suggests that reduced KCC2 activity may be involved in the mechanisms underlying increased excitability in the brains of epileptic patients. The identification of various KCC2 mutations (encoded by SLC12A5 ) has further highlighted the association between KCC2 dysfunction and the development of epilepsy [ 41 46 ]. A summary of the KCC2 mutations discovered in human epilepsy can be found in Table 1 [ 47 ], with their localization shown in Fig.…”
Section: The Role Of Kcc2 In Epileptogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that reduced KCC2 activity may be involved in the mechanisms underlying increased excitability in the brains of epileptic patients. The identification of various KCC2 mutations (encoded by SLC12A5 ) has further highlighted the association between KCC2 dysfunction and the development of epilepsy [ 41 46 ]. A summary of the KCC2 mutations discovered in human epilepsy can be found in Table 1 [ 47 ], with their localization shown in Fig.…”
Section: The Role Of Kcc2 In Epileptogenesismentioning
confidence: 99%
“…Consequently, it has been concluded that R952H is a susceptibility variant for IGE [ 44 , 45 ]. Additionally, a novel KCC2 variant, V4731, has recently been discovered in Hungarian patients with IGE [ 41 , 46 ]. The existing literature on epileptic patients with KCC2 mutations has emphasized the role of accumulated high intracellular Cl - concentration resulting from reduced KCC2-dependent Cl - extrusion, which may underlie the hyperexcitability observed in epilepsy.…”
Section: The Role Of Kcc2 In Epileptogenesismentioning
confidence: 99%
“…WES provides high-throughput outcomes at a low cost. Here, Bartha and his colleagues looked at analysis methods that would allow WES data to be used in clinical and research settings [6]. WES can detect SNVs (single nucleotide variants) and copy number variations (CNVs) are two types of genetic variations (CNVs) in the beginning, and the information gathered from both approaches can be merged and used further.…”
Section: Motivationmentioning
confidence: 99%
“…One patient had a heterozygous missense mutation in solute carrier family 12 member 5 (SLC12A5), which has been associated to idiopathic generalized epilepsy type 14. One patient had a heterozygous nonsense variation of ring finger protein 213 (RNF213), which is linked to Moyamoya disease type susceptibility [6].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation